Spanish grammar in review - Butt, John (Oxford University Press, 2000)
Oxford Easy Grammar texts cover all the fundamental and essential points of a language's grammar in a clear and user-friendly way, with every grammatical point clearly explained and backed up by examples in English before being illustrated in the foreign language. Each area of grammar is presented on a double-page spread for easy access and navigation, with all example sentences highlighted to show what is being illustrated. Finally, a full A-Z list of grammatical terms with clear descriptions rounds out each volume